Model-free predictive control for a class of switched nonlinear systems. (31st August 2022) - Tian, Ye; Wang, Yunshuo; Su, Baili; Tan, Cheng
A model-free predictive control (MFPC) method is devised towards a kind of high order discrete nonlinear switched systems whose models are undefined. Firstly, the estimation models are designed by using the compact dynamic linearisation technique and improved projection algorithm to approach the controlled nonlinear subsystems. Then, on the basis of the estimation models, the controller's explicit analytic solutions are obtained by solving the finite time domain rolling optimisation quadratic functions. Finally, an appropriate switching law is designed to make the subsystems switch reasonably in different subsystems, thus ensuring the stability of the whole system. The simulation results show that the control strategy is effective.